2012
DOI: 10.1016/j.devcel.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial GCD1 Dysfunction Reveals Reciprocal Cell-to-Cell Signaling during the Maturation of Arabidopsis Female Gametes

Abstract: Cell-to-cell communication in embryo sacs is thought to regulate the development of female gametes in flowering plants, but the details remain poorly understood. Here, we report a mitochondrial protein, GAMETE CELL DEFECTIVE 1 (GCD1), enriched in gametophytes that is essential for final maturation of female gametes. Using Arabidopsis gcd1 mutants, we found that final maturation of the egg and central cells is not required for double fertilization but is necessary for embryogenesis initiation and endosperm deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 55 publications
3
55
0
Order By: Relevance
“…Interestingly, SYCO is only expressed in the central cell, and targeted disruption of central cell mitochondria making use of a dominant version of the ATP/ADP translocator AAC2 (aac2 A199D ) represses antipodal cell death. Wu et al have expanded the picture by showing that antipodal lifespan is similarly regulated by the egg cell, as egg-cellexpressed aac2 A199D also interferes with antipodal PCD (Wu et al, 2012). These studies thus uncover a noncell autonomous role of mitochondria in the regulation of cell death and suggest that antipodal lifespan and metabolic activity of female gametes are coupled (Fig.…”
Section: Cell-cell Communication Among Female Gametophytic Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, SYCO is only expressed in the central cell, and targeted disruption of central cell mitochondria making use of a dominant version of the ATP/ADP translocator AAC2 (aac2 A199D ) represses antipodal cell death. Wu et al have expanded the picture by showing that antipodal lifespan is similarly regulated by the egg cell, as egg-cellexpressed aac2 A199D also interferes with antipodal PCD (Wu et al, 2012). These studies thus uncover a noncell autonomous role of mitochondria in the regulation of cell death and suggest that antipodal lifespan and metabolic activity of female gametes are coupled (Fig.…”
Section: Cell-cell Communication Among Female Gametophytic Cellsmentioning
confidence: 95%
“…Wu et al have in addition shown that mitochondrial function is also communicated between egg and central cell: Mutations in GAMETE CELL DEFECTIVE1 (GCD1) affect gamete maturation and antipodal cell PCD. Notably, activation of GCD1 in either egg or central cell advances the maturation in the respective other gamete, while targeted expression of aac2 A199D in the egg cell interferes with polar nuclei fusion in the central cell (Wu et al, 2012; Fig. 1K).…”
Section: Cell-cell Communication Among Female Gametophytic Cellsmentioning
confidence: 99%
“…Under our conditions, the length of the isolated antipodal cells were about 5 μm, much smaller than the length of egg cells (~30 μm) [14]. Three antipodal cells were always bound together, even in the enzyme buffer, which may be due to the interconnection via plasmodesmata [15] (Fig 2G–2I).…”
Section: Resultsmentioning
confidence: 99%
“…GCD1 mutation leads to immature egg cells, which could fuse with sperm cells and develop into an elongated zygote, but could not initiate zygote division. Expression pattern analysis revealed that both paternal and maternal GCD1 transcript could be detected in the zygote, but paternal GCD1 could not rescue the phenotype attributed by the female gcd1 mutation, suggesting that eggdeposited GCD1 is required for the onset of zygotic division (Wu et al, 2012). Thus, its role in embryogenesis could not be replaced by its paternal counterpart.…”
Section: Asymmetric Zygote Division and Its Influence On Embryogenesismentioning
confidence: 90%
“…Expression pattern analysis revealed that both paternal and maternal GCD1 could be detected in the zygote (Fig. 1A), but paternal GCD1 could not rescue the phenotype attributed by the female gcd1 mutation, suggesting that a gcd1 mutant egg is not able to sustain zygote development and initiate embryogenesis after the egg cell fused with a normal sperm cell (Wu et al, 2012). Another way parents exert influences on their offspring is through genomic imprinting, which results in monoallelic gene expression in early embryos dependent on their parent of origin.…”
Section: Influences Of the Parental Genomes On Early Embryogenesismentioning
confidence: 99%